Religion, society, and politics in France since 1789 - Tallett, Frank; Atkin, Nicholas (Hambledon Press, 1991)
This book has been carefully planned to give a coherent account of the impact of religion in France over the last two hundred years. Most books in English dealing with the subject are now dated, and in any case concentrate on institutional questions of church-state relations rather than on the wider influence of religion throughout France. These essays summarise recent French research and provide a concise up-to-date introduction to the history of modern French Catholicism.